NILAI-NILAI TASAWUF AKHLAKI DALAM GURINDAM DUA BELAS UNTUK PEMBINAAN AKHLAK SISWA MADRASAH DI ERA DISRUPSI (KAJIAN PASAL KEEMPAT GURINDAM 12 RAJA ALI HAJI) - Muhammad Abdul Ghofur (Madaris: Jurnal Guru Inovatif, 2021)
Moral problems are a matter that is of much concern to many people where the size of a nation ora society depends on the individual character they have, if the society or the nation is good then the nation and the nation are good. But if the nation's morals are damaged, the nation is considered damaged too. Examples of bad morals caused by the era of disruption are cruel, malicious, insulting, angry, deceiving, griping, rude, dirty words, and takabbur. Gurindam dua belas which is the work of the finest of Malay sons king ali haji isa literary work containing advice and wisdom about a life full of tasawuf values in it could be the solution to the decadence and moral degradation faced by a madrassa student.